A colorimetric method to quantify endo-polygalacturonase activity - Torres, Sebastián (2011)
We report a new colorimetric assay to quantify endo-polygalacturonase activity, which hydrolyzes polygalacturonic acid to produce smaller chains of galacturonate. Some of the reported polygalacturonase assays measure the activity by detecting the appearance of reducing ends such as the Somogyi–Nelson method. As a result of being general towards reducing groups, the Somogyi–Nelson method is not appropriate when studying polygalacturonase and polygalacturonase inhibitors in plant crude extracts, which often have a strong reducing power. Ruthenium Red is an inorganic dye that binds polygalacturonic acid and causes its precipitation. In the presence of polygalacturonase, polygalacturonic acid is hydrolyzed bringing about a corresponding gain in soluble Ruthenium Red. The described assay utilizes Ruthenium Red as the detection reagent which has been used previously in plate-based assays but not in liquid medium reactions. The new method measures the disappearance of the substrate polygalacturonic acid and is compared to the Somogyi–Nelson assay. The experimental results using lemon peel, a fern fronds and castor leaf crude extracts demonstrate that the new method provides a way to the quickly screening of polygalacturonase activity and polygalacturonase inhibitors in plant crude extracts containing high amounts of reducing power. On the other hand, the Ruthenium Red assay is not able to determine the activity of an exo-polygalacturonase as initial velocity and thus would allow the differentiation between endo- and exo-polygalacturonase activities.